Improving Indonesian Language Learning Outcomes Through Picture and Picture Model: Meningkatkan Hasil Pembelajaran Bahasa Indonesia Melalui Model Gambar dan Gambar - Dina Lorenza; Reni Guswita; Iri Hamzah (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Indonesian language learning at the elementary level is essential for developing students’ literacy, communication, and critical thinking skills, yet national assessments (PISA, AN) indicate persistent weaknesses in reading and comprehension. Background (Specific): At SDN 36/II Sarana Jaya, many fourth-grade students struggled with low motivation and poor outcomes in Indonesian due to monotonous lecture-based teaching. Knowledge Gap: Limited empirical evidence exists on the effectiveness of visual-based learning strategies, such as the Picture and Picture model, in improving Indonesian language outcomes at the primary level. Aim: This study aimed to improve students’ learning outcomes and engagement through the implementation of the Picture and Picture model in classroom practice. Results: Conducted as Classroom Action Research in two cycles with 25 students, the study revealed improvements in teacher performance (from 83% to 91%), student activity (from 25% to 70% in the “good” category), and learning achievement (from 35% to 90% mastery). Novelty: The study demonstrates how structured use of sequential images can scaffold comprehension, stimulate interaction, and enhance narrative skills in Indonesian. Implications: The findings suggest that Picture and Picture is an effective, replicable model for promoting literacy, active learning, and classroom engagement in elementary education.Highlight : Picture and Picture model improves student learning outcomes significantly. Student participation and engagement increase across learning cycles. Teacher performance and classroom interaction become more effective. Keywords : Learning Outcomes, Picture And Picture Model, Indonesian, Student Activity, Classroom Action